The Ability of a Single Serum Progesterone Measurement to Predict the Prognosis of First Trimester Pregnancy - Mehmet Nafi Sakar; Deniz Balsak; Sureyya Demir; Mehmet Sukru Budak; Ali Emre Tahaoglu; Sinan Emre Gungor; Emrullah Akay; Bulent Demir (Medical Network, 2020)
OBJECTIVE: There are cases where ultrasonographic evaluation is inadequate in determining first-trimester healthy pregnancy. In these cases, both the patient and the clinician are involved in a worrying expectation. The single serum progesterone measurement was tried to predict pregnancy prognosis in short time period. This study evaluated the predictive value of a single serum progesterone measurement in first-trimester pregnancy loss. STUDY DESIGN: A prospective case-control study was conducted between July 2013 and July 2014 in Tertiary Hospital. The study compared 106 patients with threatened abortion (vaginal bleeding or spotting) before 13 weeks of gestation with 110 healthy control pregnancies. Samples of serum progesterone were obtained on the day each patient was admitted to the hospital. A Beckman-Coulter macro-Enzyme-linked immunoassay (ELISA) system was used to measure serum levels of progesterone (Beckman-Coulter, Ireland). RESULTS: Progesterone levels were measured when the patients first visited the hospital and they were followed until the end of the first trimester. Progesterone levels differed significantly (p=0.013) between the two groups. The spontaneous abortion rate was significantly (p=0.044) higher in the case group. Progesterone levels differed significantly (p=0.001) between ongoing pregnancy and spontaneous abortion groups. Using a cut-off level of 10.7 ng/mL, the sensitivity, specificity, and positive and negative predictive values were 92.1%, 44%, 92.6%, and 42.3%, respectively, for viable pregnancies. CONCLUSION: A single measurement of progesterone levels in serum can predict the prognosis of a viable first-trimester pregnancy, while it is less effective for identifying non-viable pregnancies.